Uso da ciclofosfamida em modelo de imunodepressão experimental em ovinos - Garcia, M. (2004)
Cyclophosphamide (CY) was used to evaluate the effect on the immune system of sheep. Castred adult rams were divided into 3 groups, with 6 animals each one. Group I (day 0) and Group II (day 1) were treated with CY (40 mg/kg, single dose, IV), and Group III was not treated and remained as control. All groups were immunized on day 0 with B19 brucellosis vaccine. on day 6, all animals were bled and serum agglutination test for brucellosis antibodies detection was performed. During 7 days blood lymphocyte counts and electrophoresis gammaglobulin dosage were daily performed. The results showed statistical decrease of immune response. Low serum titers of brucellosis antibodies were found in Groups I and II, and lymphopenia and hypogammaglobulinemia were also found in these groups. A high mortality rate (40%) occurred in the treated animals.